Prarancangan Pabrik Dimetil Eter Proses Dehidrasi Metanol Dengan Katalis Alumina Kapasitas 20.000 Ton Per Tahun - Setiawan, Indra, Kusmiyati, S.T, M.T, Ph.D, Tri Widayatno,S.T., MS.c., Ph.D (2015)
Dimethyl ether (DME) is an alternative energy and environmentally friendly fuels including used to replace diesel fuel and LPG. Factory dimethyl ether (DME) is planned to be established in the area Bontang, East Kalimantan with a capacity of 20,000 tons / year. The raw materials used are methanol as much as 30491.34 tonnes / year from PT. Kaltim Methanol Industry in Bontang, East Kalimantan. Dimethyl ether (DME) is produced through a process of dehydration of methanol with the catalyst alumina (Al2O3) at a pressure of 14.9 atm and a temperature of 2500C. The reactor used in the manufacture of DME is multitube fixed bed reactor. The reaction is exothermic and operates on a non-isothermal non-adiabatic conditions. Product dimethyl ether (DME) that comes out of the reactor into the distillation tower purified to reach a purity of 99.5% by weight. Support unit processes used to support the factory production process consists of a water supply unit obtained from river water as much as 3284.91 kg / h, the procurement unit compressed air as much as 50 m3 / h, the unit procurement of electricity by 2,518 kW, as many as 1,593 units supplying steam , 54 kg / h, the unit procurement of diesel fuel as much as 255.7 L / h, and the laboratories used to maintain the quality of raw materials and products, to comply with the defined specifications. The company designed shape is a Limited Liability Company (PT) with line and staff organizational structure. The system is based on the division of employees working hours of employees consisting of non-shift employees and shift. Based on the results of economic analysis obtained Percent Return on Investment (ROI) before tax of 18.54% and after tax of 12.98%, Pay Out Time (POT) before tax of 3.50 years and after tax of 4.4 years, Break Even Point (BEP) of 58.25%, Shut Down Point (SDP) amounted to 29.32%, and the Discounted Cash Flow (DCF) amounted to 34.06%. Thus, the factory dimethyl ether (DME) with a capacity of 20,000 tons / year can be considered to be established in Indonesia.